Entrepreneurship Education and Academic Support: Understanding Their Impact on Entrepreneurial Motivation and Interest - Muhammad Aqshel Revinzky; M Chairul Ihsan; Cattleya Rejito; Zidny Ilma Hasan; Adhadian Akbar (Department of Business and Entrepreneurship, Faculty of Economics and Business, Universitas Negeri Makassar, 2025)
This research aims to examine the influence of entrepreneurship education and academic support on students' interest in entrepreneurship at the Faculty of Economics and Business, Universitas Padjadjaran, with entrepreneurial motivation as a mediating variable. This research uses a quantitative approach with a survey design. The research population was all students from the Faculty of Economics and Business, Universitas Padjadjaran, and the sample used was 109 students. The research results show that entrepreneurship education and academic support have a positive effect on students' entrepreneurial interest. Entrepreneurial motivation is proven to mediate the influence of entrepreneurship education and academic support on entrepreneurial interest. This research provides implications for teaching staff and lecturers to be more optimal in directing and guiding students in developing interest in entrepreneurship. By improving the quality of entrepreneurship education and comprehensive academic support, it is hoped that it can increase students' motivation and interest in entrepreneurship. For further research, efforts will be made to deepen and expand this research both in terms of variables and development of research methods.